Peran Ukuran Perusahaan dalam Memoderasi Struktur Modal dan Rasio Keuangan terhadap Kualitas Laba - Fajriannoer, Muhammad Rafly; Rafa, Wukuf Dilvan; Espa, Vitriyan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study examines the influence of capital structure, profitability, and liquidity on earnings quality and evaluates the ability of firm size to moderate these relationships within the context of the mining sector. The study adopts a quantitative paradigm, utilizing a purposive sampling method to select qualified mining sector issuers listed on the Indonesia Stock Exchange (IDX), resulting in a sample of 35 entities. The observation period spans three years (2021–2023), yielding 105 observation units. The applied data analysis technique is Moderated Regression Analysis (MRA), employing the computational facilities of the SPSS program for statistical processing. The analysis results indicate that profitability (significance value: 0.004) has a significantly adverse effect on earnings quality. Meanwhile, capital structure (significance value: 0.664) and liquidity (significance value: 0.239) show no significant impact. Furthermore, firm size is not an important moderating variable in the relationships between capital structure (significance value: 0.654), profitability (significance value: 0.275) , liquidity (significance value: 0.492), and earnings quality. These findings provide empirical contributions regarding the determinants of earnings quality in the mining sector and highlight the importance of enhanced oversight and transparency in earnings reporting.